Some anatomical aspects of Cardiac and roots of large blood vessels in one humped camel (Camelus dromadarius) - Merhish, Shaker M. (The Iraqi Journal of Veterinary Medicine, 2003)
This study use 40 specimens for one humped camel heart at the age 6 - 8 years and the specimens with their large arteries and vein roots without any harm. They have been washed and cleaned from blood and injected with latex added to it pink carmine dye (pigment). Arterial branches that feed the one humped camel heart had been studied. It proved that the heart shape in the one humped camel is wide at it’s base and narrow at it’s apex. The heart locate in thoracic cavity in inclinaing to the left. The ratio of heart weight to the body is 1.27% and the average heart weight 4810 gram and - that the average weight of the heart in the she camel this refereed to that the heart weight in 4010 gram and the male 4902 gram male is larger. this study showed that right corronary artery in the camel is big while the left corronary artery in domestic animals is small . We concluded from this study the artery branches collateral always grown from coronary artery and in a more condense that in horses, cows and sheep and veins where vena zygys disappear and the large heart artery and middle artery end at the corronary artery sinus where arterial and venal branches inter to right atrium. It is similar in cows and horses and that the papillary muscle of the heart is supplied by right and left corronary arteries in one humped camel.